Titanium sheet and method for producing the same

The titanium plate achieves high Young's modulus and excellent formability by optimizing the chemical composition and texture ratios through a controlled manufacturing process, addressing the challenges faced by industrial pure titanium plates.

JP2025038699APending Publication Date: 2025-03-19NIPPON STEEL CORPORATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023145463
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

Industrial pure titanium plates face challenges in achieving both high Young's modulus and excellent formability due to the low Young's modulus in the width direction, which is difficult to improve without compromising moldability.

Method used

A titanium plate with a specific chemical composition and metallographic structure, including a T-texture area ratio of 5-30% and a Split-TD-Texture area ratio of 30% or more, is manufactured using a hot rolling process followed by cooling, cold rolling, and annealing to achieve the desired properties.

Benefits of technology

The resulting titanium plate exhibits high Young's modulus in the width direction while maintaining excellent formability, effectively addressing the limitations of existing industrial pure titanium plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038699000001
    Figure 2025038699000001
  • Figure 2025038699000002
    Figure 2025038699000002
  • Figure 2025038699000003
    Figure 2025038699000003
Patent Text Reader

Abstract

To provide a titanium sheet made of industrial pure titanium that exhibits both excellent Young's modulus and formability.SOLUTION: The present invention provides a titanium sheet, wherein the chemical composition is, in mass%, O: 0.20% or less, Fe: 0.20% or less, N: 0.08% or less, C: 0.08% or less, H: 0.015% or less, balance: Ti and impurities; and the metal structure includes T-texture and Split-TD-Texture, with an area ratio of T-texture being 5-30%, and an area ratio of Split-TD-Texture being 30% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a titanium plate and a method for manufacturing the same. [Background technology]

[0002] Titanium plates made of commercially pure titanium are lightweight and have excellent corrosion resistance. In addition, as described in Patent Document 1, titanium plates with good formability have also been developed. For this reason, the titanium plates are used in heat exchangers, specifically, plate heat exchangers (also called "PHE"). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-316323 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the titanium plate has a problem that the Young's modulus in the plate width direction is low. On the other hand, if the Young's modulus is increased, the formability may be reduced. In addition, in order to compensate for the insufficiency of the Young's modulus, it is necessary to increase the plate thickness, so that the advantage of light weight cannot be fully utilized. Therefore, there is a problem that it is difficult to achieve both a high Young's modulus and excellent formability in the titanium plate of industrial pure titanium.

[0005] The present invention has an object to solve the above problems and to provide a titanium plate of commercially pure titanium having a high Young's modulus and excellent formability. [Means for solving the problem]

[0006] The present invention has been made to solve the above problems, and the gist of the present invention is the following titanium plate.

[0007] (1) Chemical composition, in mass%, O: 0.20% or less, Fe: 0.20% or less, N: 0.08% or less, C: 0.08% or less, H: 0.015% or less, The balance is Ti and impurities. The metal structure includes a T-texture and a Split-TD-Texture, The area ratio of the T-texture is 5 to 30%, A titanium plate having an area ratio of the Split-TD-Texture of 30% or more.

[0008] (2) The titanium plate according to (1) above, having an average crystal grain size of 5 to 100 μm.

[0009] (3) A method for producing a titanium plate according to (1) or (2) above, A hot rolling process in which the hot rolled material having the chemical composition described in (1) above is heated in a temperature range of 900 to 1050 ° C. and hot rolled to produce a hot rolled sheet; A cooling process for cooling the hot-rolled sheet until the surface temperature of the hot-rolled sheet is 300° C. or less; A cold rolling process in which the cooled hot-rolled sheet is cold-rolled at a total rolling reduction of 60% or more after the cooling process to produce a cold-rolled sheet; An annealing step of annealing the cold-rolled sheet; Equipped with A method for producing a titanium plate, wherein in the hot rolling step, the rolling reduction is 50% or more in a temperature range of 830°C or higher, and the rolling end temperature is in the range of 800 to 880°C.

[0010] (4) The method for producing a titanium sheet according to the above (3), wherein the annealing temperature T (°C) in the annealing step is in the range of 550 to 800°C, and the annealing temperature T (°C) and the holding time t (s) at the annealing temperature T (°C) satisfy the following formula (i): 20000≦(T+273.15)×(Log 10 (t) + 20) ≤ 24000 (i) Effect of the Invention

[0011] According to the present invention, a titanium plate of commercially pure titanium having a high Young's modulus and excellent formability can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present inventors have investigated the Young's modulus and formability of titanium plate made of commercially pure titanium and have obtained the following findings.

[0013] (a) In commercially pure titanium sheets, two types of textures form. One is called T-texture, and the other is called split-TD-texture. When T-texture is strongly developed, the Young's modulus in the sheet width direction increases, but the elongation decreases significantly and formability decreases. On the other hand, when split-TD-texture is strongly developed, formability improves.

[0014] (b) The inventors have found that both Young's modulus and moldability can be achieved by setting the proportions of T-texture and split-TD-texture within appropriate ranges. Specifically, it is effective to set the area proportion of T-texture in the range of 5 to 30% and the area proportion of split-TD-texture to 30% or more.

[0015] (c) In order to set the area ratios of the T-texture and split-TD-texture within the above-mentioned ranges, it is preferable to appropriately control the manufacturing conditions. For example, after heating in the β single-phase region, hot rolling is performed, and the hot rolling is completed below the β transformation point, thereby forming a certain amount of T-texture. Then, the cold rolling reduction rate and subsequent annealing conditions are controlled within appropriate ranges to develop the split-TD-texture. As a result, a structure in which the split-TD-texture is formed is obtained while leaving a certain amount of T-texture, and the area ratios of each are within the desired range.

[0016] An embodiment of the present invention has been made based on the above findings. Each requirement of the titanium plate of this embodiment will be described in detail below.

[0017] 1.Chemical composition The titanium plate of this embodiment is a commercially pure titanium plate. Here, commercially pure titanium is a titanium material that does not contain intentionally added alloy elements and is composed of impurities and Ti, and the Ti content is usually 98 mass% or more. Generally, commercially pure titanium controls strength and ductility by mainly containing small amounts of impurity elements such as O and Fe. The grain size also greatly affects these. Therefore, in order to obtain the desired characteristics, the content of the impurity elements is set to the following range.

[0018] In addition, O, Fe, N, C, and H described below are common impurity elements contained in commercially pure titanium, and their contents may be within the following ranges. In addition, in the following explanation, "%" for the content means "mass%".

[0019] O: 0.20% or less O (oxygen) improves the strength of commercially pure titanium and increases the surface hardness. However, if the O content is excessive, although the strength is improved, the formability and ductility are reduced. For this reason, the O content is 0.20% or less. The O content is preferably 0.12% or less, and more preferably 0.07% or less. On the other hand, in order to obtain the above effect, the O content is preferably 0.01% or more, and more preferably 0.02% or more.

[0020] Fe: 0.20% or less Like O, Fe (iron) is an important element for increasing the strength of industrially pure titanium. In addition, when a small amount of Fe is contained, a small amount of β phase is formed, which exerts a pinning effect, and the grain size can be stably controlled. However, if the Fe content is excessive, the β phase may precipitate too much or TiFe or the like may be formed, which may significantly reduce the formability and ductility. For this reason, the Fe content is 0.20% or less. The Fe content is preferably 0.15% or less, and more preferably 0.10% or less. On the other hand, in order to obtain the above effect, the Fe content is preferably 0.010% or more, and more preferably 0.015% or more.

[0021] N: 0.08% or less N (nitrogen) is an impurity contained in commercially pure titanium plate, and if dissolved excessively, it reduces toughness. For this reason, the N content is 0.08% or less. The N content is preferably 0.06% or less. It is preferable to reduce the N content as much as possible, but excessive reduction increases manufacturing costs. For this reason, the N content is preferably 0.0005% or more, and more preferably 0.001% or more.

[0022] C: 0.08% or less C (carbon) is an impurity contained in commercially pure titanium plate, and like nitrogen, it is an element that reduces toughness if it is dissolved in excess. For this reason, the C content is 0.08% or less. The C content is preferably 0.06% or less. It is preferable to reduce the C content as much as possible, but excessive reduction increases manufacturing costs. For this reason, the C content is preferably 0.001% or more.

[0023] H:0.015% or less H (hydrogen) is an impurity contained in commercially pure titanium plate, and if it dissolves too much, it forms hydrides and reduces toughness. For this reason, the H content is 0.015% or less. The H content is preferably 0.010% or less. It is preferable to reduce the H content as much as possible, but excessive reduction increases manufacturing costs. For this reason, the H content is preferably 0.0005% or more.

[0024] In the chemical composition of this embodiment, the balance is Ti (titanium) and impurities (elements other than those mentioned above). Here, "impurities" refers to components that are mixed in due to various factors in the raw materials and manufacturing process when industrially manufacturing titanium plates, and are acceptable within a range that does not adversely affect this embodiment. It is preferable that the content of each of the impurity elements other than those mentioned above is 0.1% or less, and the total content is preferably 0.3% or less.

[0025] 2.Metal structure In the titanium plate of the present embodiment, the metal structure includes a structure called T-texture and a structure called Split-TD-Texture. In industrially pure titanium, whose crystal structure is an hcp structure, anisotropy is large, and the characteristics differ greatly depending on the direction of the crystal grains. For example, the Young's modulus is high in the direction parallel to the c-axis direction in the hcp structure, and the Young's modulus decreases as it becomes more perpendicular to the c-axis direction.

[0026] On the other hand, when it is parallel to the c-axis direction, the ductility is low. Therefore, by forming a structure that is advantageous for improving the Young's modulus and a structure that is advantageous for improving the formability in a well-balanced manner, it is possible to improve both of the above-mentioned properties. Usually, the above-mentioned T-texture and Split-TD-texture are formed as textures. A texture refers to an assembly of crystal grains that are preferentially arranged in a specific direction, and since it is possible to control the structure as a whole assembly of crystal grains, it is effective in controlling properties.

[0027] When titanium plate is manufactured by cold rolling and annealing, which are generally performed, a large amount of split-TD-texture, which is advantageous for improving formability, is formed. On the other hand, if a large amount of split-TD-texture is formed, it is difficult to improve the Young's modulus and strength in the plate width direction. Therefore, in the titanium plate of this embodiment, the ratio of T-texture, which is advantageous for improving Young's modulus, to split-TD-texture, which is advantageous for improving formability, is set to the following range.

[0028] 2-1.T-texture area ratio In the titanium plate of this embodiment, the area ratio of T-texture is 5 to 30%. In the present application, T-texture refers to crystal grains in which the inclination between the sheet thickness direction and the c-axis is 70 to 90° and the inclination between the sheet width direction and the c-axis is in the range of 0 to 20°. In addition, T-texture is a structure that increases the Young's modulus and strength in the sheet width direction, but reduces formability.

[0029] If the area ratio of T-texture is less than 5%, it becomes difficult to obtain the desired Young's modulus. Therefore, the area ratio of T-texture is 5% or more. The area ratio of T-texture is preferably 10% or more. On the other hand, if the area ratio of T-texture exceeds 30%, moldability is significantly reduced. Therefore, the area ratio of T-texture is 30% or less.

[0030] 2-2.Split-TD-Texture area ratio In the titanium plate of this embodiment, the area ratio of the split-TD texture is 30% or more. In the present application, the split-TD texture refers to crystal grains in which the inclination between the plate thickness direction and the c-axis is 25 to 45° and the inclination between the plate width direction and the c-axis is in the range of 0 to 20°. The split-TD texture is a structure that improves formability but does not contribute to improving the Young's modulus and strength in the plate width direction.

[0031] If the area ratio of the Split-TD-Texture is less than 30%, it becomes difficult to obtain the desired formability. Therefore, the area ratio of the Split-TD-Texture is 30% or more. The area ratio of the Split-TD-Texture is preferably 35% or more. The upper limit of the area ratio of the Split-TD-Texture is not particularly limited, but is usually 70% in consideration of the manufacturing conditions, etc.

[0032] 2-3.Measuring method for each area ratio The area ratio of the T-texture or split-TD-texture mentioned above is the ratio of the T-texture or split-TD-texture to the total area measured, and is expressed as a percentage (%). The area ratio of the above-mentioned texture is measured by analyzing the crystal orientation using electron backscattering diffraction (EBSD) after chemical polishing, using a cross section perpendicular to the width direction of the titanium plate as the observation surface. Then, an area of ​​1 to 2 mm of the plate thickness is scanned in steps of 1 μm, and the area of ​​the crystal grains corresponding to the T-texture or split-TD-texture is analyzed using OIM Analysis software, and the area ratio to the observation field is calculated.

[0033] 3.Average grain size The average crystal grain size of the titanium plate of this embodiment is preferably 5 to 100 μm in order to obtain the desired formability and strength. The average crystal grain size can be calculated by performing analysis at the same time as the above-mentioned area ratio measurement.

[0034] 4.Characteristics 4-1.Young's modulus In the titanium plate of this embodiment, the Young's modulus in the plate width direction is preferably 110 GPa or more. In general cold-rolled sheets of commercially pure titanium, the Young's modulus in the plate width direction is about 100 to 110 GPa, so in this application, the target value is 110 GPa or more. The Young's modulus in the plate width direction is more preferably 112 GPa or more. The upper limit of the Young's modulus in the plate width direction is not particularly limited, but is usually 140 GPa. The Young's modulus in the plate width direction is preferably 135 GPa or less.

[0035] The Young's modulus may be measured by the following procedure. A JIS13B tensile test piece is taken from the titanium plate with the plate width direction as the longitudinal direction. A strain gauge is attached to the parallel part of the obtained test piece, and the Young's modulus is measured by repeating loading and unloading five times in the stress range of 50 to 150 MPa.

[0036] 4-2. Stretch formability In the titanium plate of this embodiment, not only the Young's modulus in the plate width direction but also the formability is improved. The formability can be evaluated by the equibiaxial stretch forming height (limit height). In the stretch forming, if the limit height (height at which the load decreases) is 18 mm or more, good formability can be obtained. The upper limit of the limit height is not particularly limited, but is usually about 25 mm.

[0037] The limit height may be measured by conducting a ball head bulging test. In the test, Naflon (registered trademark) tape TOMBO 9001, 0.05 mm thick, is used as a lubricant, and the test is performed by pushing in a ball head punch with a diameter of 40 mm and a diameter of 6 mm and a beaded die with a clearance of 2 mm and a diameter of 70 mm (inner diameter). The test conditions were a wrinkle suppression load of 7 t and a test speed of 20 mm / min, and the bulging height was measured when a crack occurred in the test piece at or near the bottom of the punch.

[0038] 5. Plate thickness From the viewpoints of rigidity and light weight, the thickness of the titanium plate of this embodiment is preferably in the range of 0.2 to 1.5 mm.

[0039] 6. Manufacturing method The titanium plate of this embodiment can be stably manufactured, for example, by the following manufacturing method.

[0040] 6-1.Hot rolling process A hot rolling material having the above-mentioned chemical composition is prepared. The hot rolling material is, for example, a slab for hot rolling. The slab for hot rolling may be one produced by dividing an ingot, or may be a rectangular slab produced by direct casting.

[0041] In the hot rolling process, after heating to the β single phase region, hot rolling is mainly performed in the β single phase region or the high temperature region of the α + β phase, and hot rolling is terminated below the β transformation point to allow sufficient formation of T-texture.

[0042] Therefore, the obtained hot rolling material is heated in the temperature range of 900 to 1050°C. If the heating temperature of the hot rolling material is less than 900°C, the temperature drop that occurs between the heating furnace and the rolls makes it impossible to manufacture under the manufacturing conditions described below. As a result, the T-texture is not sufficiently formed. In consideration of the above-mentioned temperature drop, the heating temperature of the hot rolling material is preferably about 20 to 70°C higher than the β transformation point temperature of titanium. Therefore, the heating temperature of the hot rolling material is 900°C or higher, and preferably 950°C or higher.

[0043] On the other hand, if the heating temperature of the material for hot rolling exceeds 1050°C, the hot rolling will be completed at a temperature higher than the β transformation point. In the case of the chemical composition of this embodiment, since almost no alloy elements that suppress recrystallization are contained, if the hot rolling is completed at a temperature higher than the β transformation point, recrystallization will occur in the β region and the crystal orientation will become random. As a result, a metal structure including the desired T-texture and split-TD-texture will not be formed. For this reason, the heating temperature of the material for hot rolling is 1050°C or lower.

[0044] Here, in the hot rolling process, the reduction ratio in the temperature range where the hot rolled material is 830°C or higher is 50% or more. By increasing the reduction ratio in the β single phase region or α+β high temperature region of 830°C or higher, a metal structure including the desired T-texture and split-TD-texture can be obtained. For this reason, the reduction ratio in the temperature range of 830°C or higher is 50% or more, and preferably 70% or more. The upper limit of the reduction ratio in the temperature range of 830°C or higher is not particularly limited, but when the gap between the slab and the hot rolling rolls is taken into consideration, 95% is the substantial upper limit.

[0045] In addition, the rolling end temperature in the hot rolling is in the range of 800 to 880°C. If the rolling end temperature in the hot rolling is less than 800°C, the heating temperature of the hot rolling material is inevitably low, and therefore a metal structure including the desired T-texture and split-TD-texture is not formed. For this reason, the rolling end temperature in the hot rolling is 800°C or higher. On the other hand, if the rolling end temperature in the hot rolling exceeds 880°C, the hot rolling is completed at a temperature higher than the β transformation point, and therefore a metal structure including the desired T-texture and split-TD-texture is not formed. For this reason, the rolling end temperature in the hot rolling is 880°C or lower.

[0046] In this manner, hot rolling is performed to manufacture a hot-rolled sheet. The heating temperature or rolling end temperature of the hot-rolled material in the hot rolling process can be measured by checking the surface temperature of the hot-rolled material during heating or at the end of rolling.

[0047] 6-2. Cooling process After the hot rolling process, the hot-rolled sheet obtained is cooled until the surface temperature reaches 300° C. or less. By performing such cooling, the texture can be fixed while it is formed before the recrystallization texture occurs, and the T-texture can be sufficiently formed.

[0048] Cooling is preferably performed immediately after the end of hot rolling, from a surface temperature of 700°C, preferably 750°C, more preferably 800°C, until the surface temperature is 300°C or less. Cooling is preferably performed until the surface temperature is 200°C or less, more preferably 100°C or less.

[0049] The cooling method is not particularly limited, but for example, the cooling rate until the surface temperature reaches 300° C. or less is preferably 5° C. / s or more, more preferably 10° C. / s or more, and even more preferably 30° C. / s or more. Therefore, water cooling is generally used as a cooling method, but various means can be used, such as immersing the hot-rolled sheet in a liquid such as oil, or spraying various gases including air, so-called forced air cooling. After cooling, the sheet may be wound into a coil.

[0050] 6-3.Hot-rolled sheet annealing process After the cooling step, the hot-rolled sheet may be annealed as necessary. When the hot-rolled sheet is annealed, the annealing temperature is preferably 700° C. or more and less than 850° C., and the annealing time is preferably 60 s or more and less than 600 s.

[0051] 6-4.Cold rolling process While leaving the T-texture formed in the above steps, a new split-TD-texture is formed in the cold rolling process. The thickness is reduced in the cold rolling process with a total reduction rate of 60% or more to produce a cold-rolled sheet.

[0052] If the total reduction rate in the cold rolling process is less than 60%, a sufficient amount of T-texture and split-TD-texture will not be formed. Therefore, the total reduction rate in the cold rolling process is 60% or more, and preferably 70% or more. There is no particular upper limit to the total reduction rate in the cold rolling process, but if the total reduction rate exceeds 90%, the T-texture formed in the hot rolling process or the like will easily disappear and the Young's modulus will easily decrease. Therefore, the total reduction rate is preferably 90% or less.

[0053] In addition, in cold rolling, the maximum reduction rate per run is preferably 25% or more, and cold rolling is preferably performed one or more times. The maximum reduction rate per run is more preferably 30% or more, and even more preferably 40% or more. This is because the number of cold rolling runs can be reduced. The maximum reduction rate per run refers to the maximum reduction rate among the multiple runs when cold rolling is performed multiple times, and refers to the reduction rate of that one run when cold rolling is performed only once.

[0054] In general, one pass is defined as a rolling process in which a steel sheet passes between a pair of rolls in one rolling mill, and one rolling process is defined as a series of multiple rolling passes performed without annealing. In the present application, the number of passes in the cold rolling process is not controlled, but the number of rolling passes described above is controlled.

[0055] If the number of cold rolling processes is too many, the crystal orientation becomes random due to the formation of twins, making it difficult to form split-TD-texture, and as a result, formability tends to decrease. Therefore, it is preferable to reduce the number of cold rolling processes as much as possible, since it is more efficient to reduce the number of cold rolling processes as much as possible.

[0056] In addition, annealing may be performed between cold rolling steps as necessary. This annealing is also called intermediate annealing. When intermediate annealing is performed, it is preferable to perform the annealing under the same temperature conditions as the final annealing described later.

[0057] 6-5. Annealing process After the cold rolling process, the cold-rolled sheet obtained is soaked and annealed. This annealing is also called final annealing. The annealing temperature T (°C) of the final annealing is preferably 550 to 800°C. By setting the annealing temperature within the above range, a metal structure including a desired T-texture and split-TD-texture can be obtained. In addition, the annealing temperature T (°C) and the holding time t (s) at the annealing temperature T (°C) preferably satisfy the following formula (i). 20000≦(T+273.15)×(Log 10(t) + 20) ≤ 24000 (i)

[0058] By satisfying the above formula, the grain size can be controlled to the range of 5 to 100 μm, and more preferable formability can be obtained. The annealing atmosphere is preferably a vacuum atmosphere or an inert atmosphere. After the annealing, the steel sheet can be appropriately cooled.

[0059] The titanium plate according to the present invention will be described in more detail below with reference to examples, but the present embodiment is not limited to these examples. EXAMPLES

[0060] A hot-rolled material (slab) having the chemical composition shown in Table 1 was prepared. This hot-rolled material was heated at the temperature shown in Table 2, and hot-rolled under the conditions shown in Table 2 to produce a hot-rolled sheet. The hot-rolled material was cooled until the surface temperature was 300°C or less, and wound into a coil. In Table 2, water cooling indicates a cooling rate of 20 to 40°C / s, and air cooling indicates a cooling rate of 1°C / s. In some examples, the hot-rolled sheet was annealed after cooling under the conditions shown in Table 2. Then, cold rolling and final annealing were performed under the conditions shown in Table 2 to produce a titanium sheet. In some examples, intermediate annealing was performed between cold rolling. The annealing atmosphere after cold rolling was a vacuum atmosphere or an inert atmosphere.

[0061] [Table 1]

[0062] [Table 2]

[0063] The metal structure and average crystal grain size of the obtained titanium plate were measured by the following procedures. In addition, the Young's modulus and the stretch forming height were evaluated by the following methods.

[0064] (Metal structure and average grain size) The cross section perpendicular to the width direction of the titanium plate was used as the observation surface, and after chemical polishing, the crystal orientation was analyzed using electron backscattering diffraction (EBSD). Then, an area of ​​1 to 2 mm of the plate thickness was scanned in 1 μm steps, and the area of ​​crystal grains corresponding to T-texture or Split-TD-Texture was analyzed using OIM Analysis software, and the area ratio to the observation field was calculated. The average crystal grain size was calculated by analyzing at the same time as the above-mentioned area ratio measurement.

[0065] (Young's Modulus) A JIS13B tensile test piece was taken from the titanium plate with the plate width direction as the longitudinal direction. A strain gauge was attached to the parallel part of the obtained test piece, and the Young's modulus was measured by repeatedly loading and unloading the stress in the stress range of 50 to 150 MPa five times. The Young's modulus in the plate width direction was evaluated as good when it was 110 GPa or more.

[0066] (Stretch formability) The limit height was measured by a ball head bulging test. In the test, Naflon (registered trademark) tape TOMBO 9001, 0.05 mm thick, was used as a lubricant, and the test was performed by pushing in a ball head punch with a diameter of 40 mm and a diameter of 6 mm and a beaded die with a clearance of 2 mm and a diameter of 70 mm (inner diameter). The test conditions were a wrinkle suppression load of 7 t and a test speed of 20 mm / min, and the bulging height was measured when a crack occurred in the test piece at or near the bottom of the punch. A limit height of 18 mm or more was evaluated as a good characteristic.

[0067] [Table 3]

[0068] Nos. 1 to 23, 28, 29, 31, and 33, which satisfy the requirements of this embodiment, exhibited good Young's modulus and bulging height, whereas Nos. 24 to 27, 30, and 32, which do not satisfy the requirements of this embodiment, exhibited reduced at least one of Young's modulus and bulging height.

Claims

1. The chemical composition, in mass%, is O: 0.20% or less, Fe: 0.20% or less, N: 0.08% or less, C: 0.08% or less, H: 0.015% or less, The balance is Ti and impurities. The metal structure includes T-texture and Split-TD-Texture, The area ratio of the T-texture is 5 to 30%, A titanium plate having an area ratio of the Split-TD-Texture of 30% or more.

2. The titanium plate according to claim 1, wherein the average crystal grain size is 5 to 100 μm.

3. A method for producing a titanium plate according to claim 1 or 2, A hot rolling process in which a hot rolled material having the chemical composition according to claim 1 is heated in a temperature range of 900 to 1050 ° C. and hot rolled to produce a hot rolled sheet; A cooling process for cooling the hot-rolled sheet until the surface temperature of the hot-rolled sheet is 300° C. or less; A cold rolling process in which the cooled hot-rolled sheet is cold-rolled at a total rolling reduction rate of 60% or more after the cooling process to produce a cold-rolled sheet; An annealing step of annealing the cold-rolled sheet; Equipped with The method for producing a titanium plate, wherein in the hot rolling step, the rolling reduction rate in a temperature range of 830°C or higher is 50% or more, and the rolling end temperature is in the range of 800 to 880°C.

4. The annealing temperature T (°C) in the annealing step is in the range of 550 to 800°C, and the annealing temperature T (°C) and the holding time t (s) at the annealing temperature T (°C) satisfy the following formula (i). The method for producing a titanium plate according to claim 3. 20000≦(T+273.15)×(Log 10 (t)+20)≦24000・・・(i)

Citation Information

Patent Citations

  • Pure titanium sheet having excellent formability, and method for producing the same

    JP2006316323A